2015
DOI: 10.1177/1077558715595156
|View full text |Cite
|
Sign up to set email alerts
|

Patient Characteristics Predicting Readmission Among Individuals Hospitalized for Heart Failure

Abstract: Heart failure is difficult to manage and increasingly common with many individuals experiencing frequent hospitalizations. Little is known about patient factors consistently associated with hospital readmission. A literature review was conducted to identify heart failure patient characteristics, measured before discharge, that contribute to variation in hospital readmission rates. Database searches yielded 950 potential articles, of which 34 studies met inclusion criteria. Patient characteristics generally hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
32
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 41 publications
6
32
0
Order By: Relevance
“…In our study, other factors associated with lower 9‐month readmission rates included lack of insurance coverage, DNR status and discharge home (compared to discharge to hospice or to a skilled nursing facility). Previous work has identified, amongst other factors, nonwhite race, prior hospitalizations, increased length of stay and co‐morbid cardiac or systemic disease, and HF severity as factors associated with higher readmission rates . Notably in the present study, the influence of PC on readmission remained significant whilst controlling for many of these factors, suggesting a robust role for inpatient PC in reducing readmission in HF.…”
Section: Discussionsupporting
confidence: 86%
“…In our study, other factors associated with lower 9‐month readmission rates included lack of insurance coverage, DNR status and discharge home (compared to discharge to hospice or to a skilled nursing facility). Previous work has identified, amongst other factors, nonwhite race, prior hospitalizations, increased length of stay and co‐morbid cardiac or systemic disease, and HF severity as factors associated with higher readmission rates . Notably in the present study, the influence of PC on readmission remained significant whilst controlling for many of these factors, suggesting a robust role for inpatient PC in reducing readmission in HF.…”
Section: Discussionsupporting
confidence: 86%
“…A previous study showed a relationship between nutritional status and severity in HF. 28 In the present study, it appeared that nutritional status did not reflect severity because it was possible that owing to inclusion criteria that we chose, not so many cases of severe HF were included. It was reported that ADL and NYHA in HF patients were correlated.…”
Section: Characteristics Of the Low Geriatric Nutritionalmentioning
confidence: 85%
“…27 There is a relation between cardiovascular disease history and the severity of risk factors in HF. 28 In the present study, it appeared that nutritional status did not reflect severity because it was possible that owing to inclusion criteria that we chose, not so many cases of severe HF were included.…”
Section: Characteristics Of the Low Geriatric Nutritional Risk Index mentioning
confidence: 85%
“…Indicators of need/illness level tend to have the greatest impact on health care use in empirical work (O'Connor et al. ). In our study, unmeasured aspects of patient acuity (e.g., cardiac ejection fraction) are probable confounders because, consistent with the Andersen model, they contribute to more severely ill patients being more likely to receive the treatments and to be readmitted to a hospital.…”
Section: Methodsmentioning
confidence: 99%